COMPARISON OF MORTALITY BETWEEN THE COMBINATION OF STANDARD THERAPY AND CONVALESCENT PLASMA THERAPY AND STANDARD THERAPY ONLY IN COVID-19 PATIENTS : SYSTEMATIC REVIEW AND META-ANALYSIS - Felicia Klarin; Angelica Diana Vita; Cynthia Elvira Sari Siahaan; Salsabila Nabilah Rifdah; Ayu Rahmanita Putri; Indriasti Putri Kusuma; Subur Prayitno (Journal of Community Medicine and Public Health Research)
Coronavirus Disease-19 (COVID-19) is an infectious disease caused by a newly discovered type of coronavirus. Comprehensive management for COVID-19 patients includes infection control, hemodynamic stability maintenance, oxygenation monitoring, ventilation, and pharmacotherapy administration. Convalescent plasma is one of the COVID-19 therapy choices, proven to provide relief for Ebola, SARS, and MERS patients. Therefore, the authors believed in searching data on whether convalescent plasma therapy also improves COVID-19 patients, specifically in terms of mortality. This study aims to compare the comparison in mortality between standard therapy and convalescent plasma therapy with standard therapy only in COVID-19 patients. This study used a systematic review and meta-analysis method according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. This study used ten studies that met the inclusion criteria to evaluate the comparison in mortality between the combination therapy with standard therapy only in COVID-19 patients. There was a significant difference in mortality between the combination of standard therapy and convalescent plasma therapy with standard therapy only in COVID-19 patients, and mortality in the combination therapy groups being lower than standard therapy only.